Makanan Khas Pesisir Selatan Dalam Food Photography - Wulandari, Suci; Rahmat, Aziz Fauzi (CV. ITTC INDONESIA, 2025)
This study aims to explore the richness of typical southern coastal Indonesian food through the medium of food photography as a form of cultural preservation and touristm promotion. Typical southern coastal foods such as putu kambang, mangkuak badeta, sangko cake, grilled sagun bakar, sapik cake, lokan satay lokan rendang and palai bada in this work, the aurtor uses a visual approach through food photography to highlight the uniqueness of southern coastal food in terms of appearance, color, texture, and presentation. The creative process involves field research to the southern coastal area, interviews with local culinary actors, and photo shoots that emphasize natural lighting and aesthetic composition in order to arouse the appetite and display the culinary identity. The result of the study show that food photography is effective as a visual archiving medium as well as a local culinary promotion strategy. Through attractive visualization, typical southern coastal foods can be introduced more widely and appreciated as a part of the regional cultural heritage. This work is expected to encourage the preservation of local culinary and increase the appeal of culinary tourism on the southern coast. Most of the techniques used by the author in the process of taking eve angle and flat lay angle. In working on this work, the author has conducted exploration, preparation, and design. The process of creating this final assignment went thourgh several stages including preparation, realization, and selection of works. The author carried out an editing process to perfect this final assignment. The works numbered 20 with 24 photos that had been selected by the supervisor.